From Ottoman Caliphate to League of Eastern Nations: Egyptian Easternist Worldmaking in the Late and Post-Ottoman Age - Olesen, Mattias Gori (Die Welt des Islams, 2026)
The abolition of the Ottoman Caliphate in 1924 represented a critical juncture in Muslim thought and has often been seen as succeeded by a widespread turn to territorial nationalism. This article contributes to the growing scholarship that has underlined the more conflictual and ambivalent nature of post-Ottoman Muslim thought by focusing on the case of Easternism (al-Fikra al-Sharqiyya), an Egypt-centered intellectual community and network that envisioned the Muslim world as part of a larger "East" and a "worldmaking" project of anticolonial cooperation from North Africa to Japan. Drawing on a range of intellectual writings and intelligence sources, the article outlines the history of Easternism from the late Ottoman era into the 1930s and argues that while Easternism interlaced with more well-known modes of Muslim thought - such as Ottomanism, pan-Islamism, Islamic reform, territorial nationalism and Arab nationalism - it still managed to come into its own as a distinct vision.